Instrument, Policy or Strategy? The Ambiguity of Popular Culture - Tauschek, Markus (Austrian Journal of Historical Studies, 2016)
This article examines the various ways reflexive or “knowing subjects” (Giddens) negotiate, perform and generally use popular culture today. Therefore, the article, following the idea of asymmetrical comparison, discusses three case studies from very different fields – a local protest movement against a furniture store, a Gothic festival in Leipzig and the pageant for a new national anthem in Switzerland – in order to find and deconstruct parallels and differences in the ways popular culture is constructed and conceptualized. Finally, the article discusses whether popular culture, which can be interpreted as polyvalent, is a powerful instrument, a means of policy or a target-oriented strategy.